Efeito da pressão positiva aguda na cavidade nasal - Balsalobre Filho, Leonardo Lopes [UNIFESP] (2018)
Introduction: Many studies have shown the influence of nasal obstruction on sleep disorders and adaptation to continuous positive airway pressure (CPAP). However, data are lacking on the impact of continuous positive pressure on the nasal cavity – whether in healthy individuals or patients with allergic rhinitis – and on the effect, if any, of topical corticosteroids on nasal patency after exposure to CPAP. In addition, it has been hypothesized that increasing interstitial hydrostatic pressure within the sinonasal mucosa of patients with nasal polyposis may decrease polyp size. Objective: The overarching goal of this series of studies was to evaluate the effect of continuous positive pressure on the nasal cavity of healthy individuals, subjects with allergic rhinitis, and subjects with nasal polyposis by objective and subjective methods. Methods: Three studies were carried out. The first included 27 subjects who were exposed to 2 hours of positive nasal pressure by CPAP via nasal mask with a pressure of 20 cm/H2O. A questionnaire on nasal allergic symptoms was applied, and participants were subsequently divided into two groups: with and without nasal allergic symptoms. Four methods were applied immediately before and after exposure to positive pressure: a visual analogue scale (VAS) of nasal obstruction; the Nasal Obstruction Symptom Evaluation (NOSE) scale; peak nasal inspiratory flow (PNIF) measurement; and acoustic rhinometry (AcRh). For the second study, 10 patients with nasal allergic rhinitis were exposed to 1 hour of positive nasal pressure by CPAP via nasal mask with a pressure of 15 cm/H2O. VAS, NOSE, PNIF, and AcRh measurements were obtained immediately before exposure to positive pressure. Topical intranasal budesonide therapy (400 mcg/day) was administered for 4 weeks, and the aforementioned tests were performed again, now before and after exposure to positive pressure. For the third study, 12 patients with nasal polyposis and 27 controls without polyposis were exposed to CPAP (20 cm/H2O) for 2 hours. VAS, NOSE, PNIF, AcRh, and nasal endoscopy (for polyp grading with the Meltzer Clinical Scoring System) were performed before and after the intervention. Results: In the first study, an increase in nasal obstruction was observed both on subjective parameters (VAS and NOSE) and on objective evaluation (reduction of nasal cavity volume on AcRh and lower PNIF). Deterioration of indicators of nasal patency was worse in subjects with nasal allergic complaints. In the second study, comparison of VAS, NOSE, PNIF, and AcRh findings after and before topical budesonide therapy and after exposure to positive pressure showed a statistically significant improvement in nasal obstruction scores and indicators of nasal patency. In the third study, for the polyposis group, VAS, NOSE and AcRh findings did not differ significantly (p=0.72, p=0.73, and p=0.17, respectively), but PNIF worsened (p=0.04) after exposure to CPAP. There was a statistically significant reduction in nasal polyp volume (p=0.04). The control group experienced deterioration of all measured parameters of nasal obstruction. Conclusion: Acute exposure to positive pressure via CPAP impairs nasal patency. This effect is even more pronounced in individuals with nasal allergic symptoms. Topical corticosteroid therapy was able to mitigate the irritant effects of CPAP on the nasal mucosa, leading to improvement of nasal patency parameters. In patients with nasal polyposis, CPAP exposure reduced the size of nasal polyps, but also reduced nasal patency as measured by PNIF. However, it had no significant effects on acoustic rhinometry findings or clinical symptoms of nasal obstruction.